Timed Up and Go Test Performance as an Indicator of Fall History in Institutionalized Elderly: A Pilot Study. Issue 4 (October 2017) - Millán-Calenti, José C.; Núñez-Naveira, Laura; Lorenzo-López, Laura; Rodríguez-Villamil, José L.; Muñoz-Mendoza, Carmen L.; Cabañero-Martínez, M. José; Cabrero-García, Julio; Maseda, Ana
Abstract : Background: Ageing is associated with sensory and physical declines and falling risk. Objective: To determine the association between 3 performance-based mobility tests and fall history. Methods: Fifty participants' mobility was assessed by Timed Up and Go (TUG) and 4- and 6-m walking tests (WT). Results: The TUG performance correlated with 4- and 6-m WT performance, and performance on 4-m WT positively correlated with 6-m WT. Only TUG performance showed a strong relationship to fall history. Conclusions: Performance tests could indicate the presence of fall history in the institutionalized older adults; the TUG being the most suitable compared with other common WT.